2015
DOI: 10.1007/s12110-015-9251-6
|View full text |Cite
|
Sign up to set email alerts
|

The Complexity of Jokes Is Limited by Cognitive Constraints on Mentalizing

Abstract: Although laughter is probably of deep evolutionary origin, the telling of jokes, being languagebased, is likely to be of more recent origin within the human lineage. In language-based communication, speaker and listener are engaged in a process of mutually understanding each other's intentions (mindstates), with a conversation minimally requiring three orders of intentionality. Mentalizing is cognitively more demanding than non-mentalizing cognition, and there is a well-attested limit at five orders in the lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…A similar patterns were observed in older (Bischetti et al 2019) and younger typical adults (Samson 2012). Along the lines of Dunbar et al (2016), a possible explanation is that mental jokes, although not associated with higher difficulty in the comprehension accuracy measure, are heavier in terms of cognitive processing because of their mentalistic content, and the higher effort spent in processing might induce stronger reactions (i.e., higher funniness ratings).…”
Section: Discussionsupporting
confidence: 61%
“…A similar patterns were observed in older (Bischetti et al 2019) and younger typical adults (Samson 2012). Along the lines of Dunbar et al (2016), a possible explanation is that mental jokes, although not associated with higher difficulty in the comprehension accuracy measure, are heavier in terms of cognitive processing because of their mentalistic content, and the higher effort spent in processing might induce stronger reactions (i.e., higher funniness ratings).…”
Section: Discussionsupporting
confidence: 61%
“…This makes sense since very short headlines (4-5 words long) barely have enough contextual information to exploit to make a humorous edit, whereas headlines that have very rich contexts generally allow editors more flexibility to generate humor. We note that Dunbar et al (2016) also found that longer jokes are funnier, but that some jokes could be too complicated to be funny.…”
Section: Length Of Jokementioning
confidence: 62%
“…The answer seems to be probably no: laughter needs a trigger, and this has to be either physical (slapstick) or verbal (jokes), while jokes depend on significantly higher levels of cognitive processing (Dunbar, Launay, & Curry, 2016) than archaic humans could aspire to (Pearce, Stringer, & Dunbar, 2014;Dunbar, 2014a). However, if wordless chorusing began to be used to allow communal chorusing on a conversational or even camp-wide scale, it would have provided a natural template for the evolution of voiced speech, and hence language, by the very short additional step of mapping meaning onto sound (as originally proposed by Darwin 1871 andJespersen 1922).…”
mentioning
confidence: 99%